2010
DOI: 10.2217/nnm.10.67
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Curcumin Conjugate-Forming Nanoparticles as Anticancer Prodrug and Drug Carriers: In Vitro and In Vivo Effects

Abstract: Curcumin has been shown to have high cytotoxicity towards various cancer cell lines, but its water insolubility and instability make its bioavailability exceedingly low and, thus, it is generally inactive in in vivo anticancer tests. Here, we report an intracellular-labile amphiphilic surfactant-like curcumin prodrug--curcumin conjugated with two short oligo(ethylene glycol) (Curc-OEG) chains via beta-thioester bonds that are labile in the presence of intracellular glutathione and esterase. Curc-OEG formed sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 45 publications
1
52
0
Order By: Relevance
“…Previous attempts at encapsulating curcumin in liposomes, phospholipid complexes, or other nanoparticle-based technologies have been reported, showing an improvement in water dispersibility and a longer circulation time (Tang et al, 2010;Duan et al, 2010;Kim et al, 2011) A possible nanosized delivery system is constituted by naturally available clay halloysite nanotubes (HNT). Halloysite has been found a viable and inexpensive nanoscale container for the encapsulation of biologically active molecules such as biocides and drugs, as Price et al (2001) first demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts at encapsulating curcumin in liposomes, phospholipid complexes, or other nanoparticle-based technologies have been reported, showing an improvement in water dispersibility and a longer circulation time (Tang et al, 2010;Duan et al, 2010;Kim et al, 2011) A possible nanosized delivery system is constituted by naturally available clay halloysite nanotubes (HNT). Halloysite has been found a viable and inexpensive nanoscale container for the encapsulation of biologically active molecules such as biocides and drugs, as Price et al (2001) first demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous attempts at encapsulating curcumin in liposomes, phospholipid complexes, and other nanoparticle-based technologies have been reported, which appear to provide better water dispersibility and a longer circulation time. [10][11][12][13][14] A key attribute of an optimal drug delivery system for cancer is the ability to treat tumors effectively with minimal side effects. In addition to having good solubility in water and stability, increased drug permeability and improved antitumor activity in vivo are also important factors.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Researchers have also investigated nanoscale formulations of curcumin, such as liposomes, microemulsions, and micelles, for potential therapeutic applications. [37][38][39][40][41][42] The nanoscale effect by which such drug delivery systems improve the oral performance of curcumin involves increasing the surface area and interactions of curcumin, thereby providing better water dispersibility to enhance its absorption. 38 In this study, a novel silica-coating liposomal strategy was used to construct a nanohybrid formulation for curcumin.…”
Section: Resultsmentioning
confidence: 99%